2004
DOI: 10.1038/nature02329
|View full text |Cite
|
Sign up to set email alerts
|

The candidate tumour suppressor protein ING4 regulates brain tumour growth and angiogenesis

Abstract: Gliomas are the most common primary tumours of the central nervous system, with nearly 15,000 diagnosed annually in the United States and a lethality approaching 80% within the first year of glioblastoma diagnosis. The marked induction of angiogenesis in glioblastomas suggests that it is a necessary part of malignant progression; however, the precise molecular mechanisms underlying the regulation of brain tumour growth and angiogenesis remain unresolved. Here we report that a candidate tumour suppressor gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
416
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 335 publications
(446 citation statements)
references
References 20 publications
29
416
1
Order By: Relevance
“…Two recent publications have highlighted oncogenic alterations in signaling pathways (trkAIII, ING4) causing dysregulated constitutive NF-kB activation which resulted in increased survival, growth, and angiogenesis of brain tumors. 54,55 A novel alternative splice variant of trkA, termed trkAIII, was identified with expression restricted to neural progenitor cells, neuroblastomas, and other neural crest-derived tumors. TrkAIII is constitutively active in a ligand-independent fashion, and was found to continuously induce activation of NF-kB in neuroblastoma cell lines.…”
Section: Cell Survival and Disease Oncogenesis And Tumor Promotionmentioning
confidence: 99%
“…Two recent publications have highlighted oncogenic alterations in signaling pathways (trkAIII, ING4) causing dysregulated constitutive NF-kB activation which resulted in increased survival, growth, and angiogenesis of brain tumors. 54,55 A novel alternative splice variant of trkA, termed trkAIII, was identified with expression restricted to neural progenitor cells, neuroblastomas, and other neural crest-derived tumors. TrkAIII is constitutively active in a ligand-independent fashion, and was found to continuously induce activation of NF-kB in neuroblastoma cell lines.…”
Section: Cell Survival and Disease Oncogenesis And Tumor Promotionmentioning
confidence: 99%
“…Accumulating evidence suggests that NF-kB also contributes to brain cancer, as a novel trkAIII splice variant of the neurotrophin tyrosine kinase receptor type 1 (TrkA) was shown to oppose growth-restricting nerve growth factor (NGF)/TrkAI signaling in neuroblastoma and to stimulate tumor-promoting signaling via PI3K/Akt and NF-kB (Tacconelli et al, 2004). The tumor suppressor inhibitor of growth family member isoform 4 (ING4), whose inactivation in brain tumors is associated with increased survival, growth and angiogenesis, reportedly interacts with RelA and leads to transcriptional repression of NF-kB-dependent genes (Garkavtsev et al, 2004). NF-kB activation has also been implicated along with Akt in high-grade glioma .…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectmentioning
confidence: 99%
“…Whereas PPARg is commonly involved in activating transcription, its sumoylation promotes retention of repressor complexes on NF-kB-dependent proinflammatory genes like those encoding TNF and inducible nitric oxide synthase (iNOS) (Bailey and Ghosh, 2005;Pascual et al, 2005). The candidate tumor suppressor ING4 physically associates with RelA and regulates brain tumor growth and angiogenesis by suppressing NF-kB DNA binding to antagonize expression of NF-kB-dependent expression of the proangiogenic interleukin-8 gene (Garkavtsev et al, 2004). Future studies will determine whether ING4 exerts similar effects on anti-or proapoptotic genes that are under NF-kB's transcriptional control.…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…ING4, a novel member of the ING family, has recently emerged as a strong tumor suppressor gene that functions in cell proliferation, contact inhibition, and angiogenesis (Garkavtsev et al, 2004;Kim et al, 2004). ING4, along with ING5, was first isolated and characterized through a computational search of ING1 sequence homology .…”
mentioning
confidence: 99%
“…It maps to human chromosome 12p13-31, including 8 exons and 7 introns, and encodes a 248 amino acid polypeptide. ING4 is a nuclear factor expressed in normal human tissues, but its expression is markedly reduced in astrocytic neoplasms, such as human gliomas, with levels inversely correlated with the tumor grade (Garkavtsev et al, 2004). Previous studies demonstrated that overexpression of ING4 could induce a decreased cell population in the S phase of the cell cycle and apoptosis in a p53-dependent manner with increasing p21 expression in RKO cells .…”
mentioning
confidence: 99%